PENGARUH MANAJEMEN LESSON STUDY BERBASIS SEKOLAH DAN SUPERVISI AKADEMIK KEPALA SEKOLAH TERHADAP KINERJA MENGAJAR GURU SD DI KECAMATAN WOYLA TIMUR, ACEH BARAT - Rustam Zaini; Marwan Marwan; Saiful Bahri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2026)
This study aimed to examine the effects of School-Based Lesson Study (SBLS) management and principals’ academic supervision on the teaching performance of elementary school teachers in Woyla Timur District, West Aceh Regency. A quantitative survey design was employed. The study involved a population of 98 elementary school teachers, all of whom were selected as the research sample using a total sampling technique. Data were collected through questionnaires and analyzed using simple and multiple linear regression. The findings revealed that School-Based Lesson Study management had a positive and significant effect on teachers’ teaching performance (r = 0.312, p = 0.005). Likewise, principals’ academic supervision showed a positive and significant effect on teaching performance (p 0.001). Simultaneously, School-Based Lesson Study management and academic supervision significantly influenced teachers’ teaching performance (p 0.001). These findings indicate that collaborative implementation of School-Based Lesson Study enhances lesson planning and instructional practices, while supportive academic supervision strengthens teachers’ professional competence. The synergy between these two factors contributes to sustainable improvements in teaching performance, particularly in elementary schools located in rural areas.